PENGARUH SALES PROMOTION DAN STORE ATMOSPHERE TERHADAP IMPULSIVE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL INTERVENING PADA DECO MART KUALA TANJUNG - Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin (ITB AAS Indonesia Surakarta, 2023)
This research aims to determine the effect of sales promotion and store atmosphere on impulsive buying with positive emotion as an intervening variable at Deco Mart Kuala Tanjung. The research method used is a quantitative method using the help of Smart PLS version 3.0 which was collected from the results of distributing questionnaires to 96 Deco Kuala Tanjung consumers. The analytical method used in this research is using instrument tests, namely validity and reliability tests. measurement model (outer model), namely validity test, reliability test, then the structural model (inner model) includes: coefficient of determination/r-square (r2), goodness of fit model and hypothesis testing with the t-statistic test and indirect effect test (influence indirect). The results of Smart PLS 3.0 in this research are that Sales Promotion has an effect on Positive Emotion, Store Atmosphere has an effect on Positive Emotion, Sales Promotion has an effect on Impulse Buying, Store Atmosphere has an effect on Impulse Buying, Positive Emotion has no effect on Impulse Buying, Sales Promotion has no effect on Impulse Buying, Sales Promotion has no effect on Impulse Buying. Keywords : Sales Promotion, Store Atmosphere, Impulse Buying, Possitive Emotion.